Fever in the recently returned HIV infected traveller. Issue 2 (30th March 2004) - Birnie, A; Gazzard, B G; Bacon, C; Dogan, A; Shaw, P J; Miller, R F
Abstract : A 41 year old HIV infected man with an extensive travel history developed intermittent fever and weight loss shortly after returning from abroad. Extensive and prolonged investigation identified the cause.